Viscosity of chalcogenide glass-formers - Košťál, Petr; Shánělová, Jana; Málek, Jiří (Taylor & Francis Ltd., 2020)
Chalcogenide glass-formers are being used in a remarkable range of various optoelectronic, photonics, photoconducting, sensing and memory device applications. The knowledge of viscosity is essential for the processing of any glass-forming material, in particular for the fabrication of precise optical elements, which is the main application field of chalcogenide glasses. This work presents an extensive collection of all available viscosity data for chalcogenides, including the measurement methods. The Mauro-Yue-Ellison-Gupta-Allan (MYEGA), Arrhenius and VFT equations are used to fit the temperature dependences of viscosity. The viscosity glass transition temperatures, fragilities and apparent activation energies are calculated from these fits. Consequently, these parameters are discussed with regard to the compositional evolution of the respective chalcogenide systems.
Viskozita chalkogenidových sklotvorných systémů
Keywords: Viscosity; Viscous flow; Chalcogenide; Fragility; Glass transition; Viskozita; Viskózní tok; Chalkogenidy; Fragilita; Skelný přechod